# Yahoo Web Search

1. Sort by

...any duplicate numbers in Step 2. That will be: n((T ∩ K) ∪ C) I think this is what you asked for. forming.

1 Answers · Science & Mathematics · 21/02/2017

2. ### Help with math question?

i) c_k(A+B) = c_k(A)+c_k(B), because every element of A... the addition of the k-th columns of A and B. ii) c_k(λA) = λ c_k(A), because (λA)_ij = λ A_ij, and therefore...

1 Answers · Science & Mathematics · 16/03/2013

3. ### Sum of Reciprocals of Triangular Numbers?

k = (n+1)_C_2 = (n+1)(n)/2 1/k = 2/((n+1)(n)) = 2(1/((n+1)(n))) ... (expanding the...n+1)/((n+1)(n))-(n)/((n+1)(n)) = 2(1/n - 1/(n+1)) So... Σ1/k = Σ 2(1/n - 1/(n+1)) = 2 Σ (1/n - 1/(n+1)) Because...

5 Answers · Science & Mathematics · 18/12/2008

4. ### In triangle ABC, a=8, b=15, K(area)=36. Find c.?

square root of 481? or square root of 97? Either one works.

5 Answers · Science & Mathematics · 14/04/2008

5. ### CAN SOMEONE HELP ME ASAP (k+2)x^2-kx-2=0?

ax^2 + bx +c = 0 the discriminant is b^2 - 4ac a = k + 2 b = -k c = -2 (-k)^2 - 4(k + 2) * -2 >= 0 k^2 + 8k + 16 >= 0 (k + 4)^2 >= 0 k + 4 >=0 k >= -4 for real roots

2 Answers · Science & Mathematics · 28/09/2014

K-C-C the signs of -(+4), and we have: -3 + (-4) = -7 I hope this helps!

2 Answers · Science & Mathematics · 09/04/2011

7. ### How do you change a function from the form *y=x^2 + bx + c* to the form *y=a(x - h)^2 + k*?

... remaining constants are then added to get k (in this case -9 + 8 = -1).

1 Answers · Science & Mathematics · 28/11/2009

8. ### for what values of k will the function f(x)=kx^-4x+k have no zeros?

...k For no zeros, b^2 < 4ac where b = -4, a = k and c = k So (-4)^2 < 4 x k x k 16 < 4k^2 4...

3 Answers · Science & Mathematics · 23/01/2012

9. ### The following message was coded using c = 17x + 3. How to decode the message?

... A X K Z K N J J K C E X Q I Z V If you don t know the...

1 Answers · Science & Mathematics · 01/02/2016

10. ### Using binomial theorem find and simplify?

(a + b)^n = ∑[k=0,n] C(n,k) a^(n-k)b^k so the coefficient of the a^20b^7 for (a − b... at C(27,7) a^(27-7)(-b)^7 now (x+1)^11 = C(11,k) *x^(11-k)(1)^k so for that we want a k value of 3 => 11...

2 Answers · Science & Mathematics · 03/05/2014